Biophysical and socioeconomic aspects of the Páez river sub-basin, Cartago, Costa Rica. - Alvarez Jiménez, María (2021)
The present study consisted in a characterization of biophysical and socioeconomic variables of the Páez River sub-basin, located in the norther sector of the city of Cartago, Costa Rica, with the purpose of generating baseline knowledge aimed at facilitating actors with decision-making tools and to propose water resource management guidelines for their eventual implementation. Quantitative and qualitative research techniques were used, including the application of a survey to 178 people in 10 localities geographically distributed in the upper, middle and lower sections of the sub-basin. The Páez River sub-basin covers an area of 28.34 km2 in the cantons of Oreamuno and Paraíso and over 50% of the territory is dedicated to agricultural activities and 16% to forest coverage. This geographical region presents important problems such as climatic vulnerability environmental pollution, governance issues, deficient diversification of economic activities, and thus poor diversity of employment opportunities in the region. The role of the Páez River sub-basin as a fundamental component for the supply of potable water and water for the development of productive activities is evidenced, the proposed characterization provides a baseline for determining adequate basin management methodologies.